Degenerative effect of Ankaferd Blood Stopper® on mice peripheral sensory neurons in vitro - Üstün, Ramazan; Oğuz, Elif Kaval (Folia Neuropathologica, 2018)
Ankaferd Blood Stopper® (ABS) is a licensed medicinal herbal extract that ensures effective hemostasis on external, internal, postoperative and dental bleeds. Dorsal root ganglia (DRG) harbor cell bodies of peripheral sensory neurons. DRG neurons receive peripheral information and regularly send projections to nuclei in the brainstem and the spinal cord. These neurons play critical roles in neural development. Neuronal dysfunctions were reported due to ABS use in surgical interventions. The purpose of this experiment was to investigate the degenerative effects of the ABS on mice DRG cells in vitro . DRG neurons were isolated from adult mice and cultured in vitro . The neurons were incubated with various concentrations of ABS for 24 h. At the end of 24 hours, under fluorescence microscopy, cell viability was determined with the fluorescent dye calcein-AM, and cell death was determined with the fluorescent dye propidium iodide. The behavior of the cells was displayed with time-lapse video microscopy for 12 hours from the time of treatment. ABS killed both neurons and non-neuronal cells via necrosis at a concentration of 25 µl/ml or more. ABS has the degenerative effect on mice peripheral sensory neurons, depending on the ABS level.